Submodularity in economics - Kovalev, Mikhail M.; Koroleva, Anna A. (Journal of the Belarusian State University. Economics, 2024)
It is shown that submodularity simplifies the optimisation of economic processes. The main properties of submodular and strongly submodular functions and their connection with trends in economic processes (negative synergy and interchangeability) are established. Classes of problems in economics modeled by submodular functions are described. The contribution of submodularity to economic decision-making is demonstrated.